Direct Observation of Teacher and Student Behavior in School Settings: Trends, Issues and Future Directions. (August 2014) - Lewis, Timothy J.; Scott, Terrance M.; Wehby, Joseph H.; Wills, Howard P.
Across the modern history of the field of special education and emotional/behavioral disorders (EBD), direct observation of student and educator behavior has been an essential component of the diagnostic process, student progress monitoring, and establishing functional and statistical relationships within research. This article provides an overview of the importance of direct observation in the field of EBD and current direct observation strategies and behavioral targets, as well as an analysis of the strengths and limitations of direct observation. Recommendations, including the possible expansion of traditional direct observation metrics, are discussed.